Gaps, barriers and bottlenecks to sustainable land management (SLM) adoption in Uganda - N. Banadda (African Journal of Environmental Economics and Management, 2019)
Land degradation is a global problem and a great challenge to sustaining the biological, economic and social services provided by various ecosystems. This work assessed the causes of land degradation in Uganda and identified gaps, barriers and bottlenecks that hinder sustainable land management programmes adoption. The major human-induced types of land degradation in Uganda included soil erosion, soil fertility decline and habitat loss. The findings of this study also point to the fact that, the decline in soil fertility affected about 88% of the rural population that subsist on less than 2 ha per family constituting over three million small-scale holdings. In addition, this work traced the various policies, plans, programmes and strategic frameworks formulated during the period of economic growth in Uganda and assessed the main constraints therein that hinder up/out scaling best land management practices.